Values Of Religious Education in Begalan Tradition from Banyumas District, Central Java Province - Rachmadhani, Arnis (PUSAKA, 2021)
Begalan is an original tradition of Banyumas, Central Java which is performed in a series of wedding ceremonies. Begalan is a combination of dance, speech, and comedy, which is performed with musical accompaniment. The Begalan tradition contains the values of religious education which is full of advice and teaching. Community life is closely related to culture or tradition, including Javanese culture. The interrelation between Islamic teachings and Javanese culture includes the meaning of the contents of brenong kepang, including ilir, ian, cething, kusan, centhong, irus, siwur, tampah, pari, ciri-muthu, suket, suluh, kendil, and broom stick. In each of these household appliances, there is a meaning of religious knowledge. This research was conducted with a qualitative approach. Data obtained through interviews, observation, documentation, and FGD. The purpose of this study was to reveal the values of religious education in the begalan tradition along with the preservation challenges it faces. The begalan tradition has Islamic educational values, such as the value of monotheism education, the value of religious education, the value of moral education, and the value of social education. Everything related to this tradition certainly needs to be done by all parties so that this divine heritage can be preserved and not extinct.